2016
DOI: 10.1016/j.pmrj.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Health‐Related Quality of Life Components in Children With Neonatal Brachial Plexus Palsy: A Qualitative Study

Abstract: Not applicable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Children with NBPP have the perception that limited ROM and reduced strength affect their performance of certain movements in sports or school activities. 3,12,13 In the current study, however, parents were the ones who showed reduced perception in the sports and physical function domain. In Kirjavainen et al, 12 NBPP children (n=79; 71%) had limitations in performing activities such as cycling, cross-country skiing, and swimming.…”
Section: Nbppg Mean±sdmentioning
confidence: 55%
See 2 more Smart Citations
“…Children with NBPP have the perception that limited ROM and reduced strength affect their performance of certain movements in sports or school activities. 3,12,13 In the current study, however, parents were the ones who showed reduced perception in the sports and physical function domain. In Kirjavainen et al, 12 NBPP children (n=79; 71%) had limitations in performing activities such as cycling, cross-country skiing, and swimming.…”
Section: Nbppg Mean±sdmentioning
confidence: 55%
“…10,11 In this domain, lower scores were obtained for tasks that required upper limbs use, as limited ROM affected the functionality of such children. 13 On the parents' perception, NBPPG children have more pain than the unaffected controls. The pain domain was assessed using the CHQ and PODCI, higher perceptions of pain were reported by parents of NBPP children in the CHQ alone.…”
Section: Nbppg Mean±sdmentioning
confidence: 99%
See 1 more Smart Citation
“…Topics that have emerged from qualitative analyses include body image and self-esteem (Chang et al, 2016), as well as emotional impact, thoughts about future, and coping with social situations (Skjerning, Mahon, Husby, & DunnGalvin, 2014). If we assume that the focus groups were able to collect the full range of experiences of short stature in each country, then differences in the number of statement categories could be a sign of differences in experience between countries.…”
Section: Discussionmentioning
confidence: 99%
“…Socioemotional issues play an important role in children with chronic conditions, as suggested by studies that used focus groups to assess HrQoL in children with chronic conditions like celiac disease or neonatal brachial plexus palsy (Chang et al, ). Topics that have emerged from qualitative analyses include body image and self‐esteem (Chang et al, ), as well as emotional impact, thoughts about future, and coping with social situations (Skjerning, Mahon, Husby, & DunnGalvin, ). If we assume that the focus groups were able to collect the full range of experiences of short stature in each country, then differences in the number of statement categories could be a sign of differences in experience between countries.…”
Section: Methodsmentioning
confidence: 99%